Effects of Minerals on Resistance of Bacillus subtilis Spores to Heat and Hydrostatic Pressure - Igura, Noriyuki (American Society for Microbiology, 2003)
Among Bacillus subtilis IFO13722 spores sporulated at 30, 37, and 44°C, those sporulated at 30°C had the highest resistance to treatments with high hydrostatic pressure (100 to 300 MPa, 55°C, 30 min). Pressure resistance increased after demineralization of the spores and decreased after remineralization of the spores with Ca(2+) or Mg(2+), whereas the resistance did not change when spores were remineralized with Mn(2+) or K(+), suggesting that former two divalent ions were involved in the activation of cortex-lytic enzymes during germination.